The dominant role of mergers in the size evolution of massive early-type galaxies since z ~ 1 - López-Sanjuan, C; Fèvre, O; Ilbert, O; Tasca, L; Bridge, C; Cucciati, O; Kampczyk, P; Pozzetti, L; Xu, C; Carollo, C; Contini, T; Kneib, J; et al. (2012)
In this paper we measure the merger fraction and rate, both minor and major, of massive early-type galaxies (M_star >= 10^11 M_Sun) in the COSMOS field, and study their role in mass and size evolution. We use the 30-band photometric catalogue in COSMOS, complemented with the spectroscopy of the zCOSMOS survey, to define close pairs with a separation 10h^-1 kpc <= r_p <= 30h-1 kpc and a relative velocity Delta v <= 500 km s^-1. We measure both major (stellar mass ratio mu = M_star,2/M_star,1 >= 1/4) and minor (1/10 <= mu < 1/4) merger fractions of massive galaxies, and study their dependence on redshift and on morphology. The merger fraction and rate of massive galaxies evolves as a power-law (1+z)^n, with major mergers increasing with redshift, n_MM = 1.4, and minor mergers showing little evolution, n_mm ~ 0. When split by their morphology, the minor merger fraction for early types is higher by a factor of three than that for spirals, and both are nearly constant with redshift. Our results show that massive early-type galaxies have undergone 0.89 mergers (0.43 major and 0.46 minor) since z ~ 1, leading to a mass growth of ~30%. We find that mu >= 1/10 mergers can explain ~55% of the observed size evolution of these galaxies since z ~ 1. Another ~20% is due to the progenitor bias (younger galaxies are more extended) and we estimate that very minor mergers (mu < 1/10) could contribute with an extra ~20%. The remaining ~5% should come from other processes (e.g., adiabatic expansion or observational effects). This picture also reproduces the mass growth and velocity dispersion evolution of these galaxies. We conclude from these results that merging is the main contributor to the size evolution of massive ETGs at z <= 1, accounting for ~50-75% of that evolution in the last 8 Gyr. Nearly half of the evolution due to mergers is related to minor (mu < 1/4) events.